PENERAPAN MODEL INTERAKSI PROMOTIF (FACE TO FACE PROMOTIVE INTERACTION) DALAM PEMBELAJARAN - Dahniar (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Learning is a process of interaction between students and teachers as well as students and students who give a good influence. The success of learning is influenced by various factors, one of which is the application of a good learning model and in accordance with the conditions of students. Learning that can help students in learning is the cooperative learning model of Promotive Interaction (Face to Face Promotive Interaction. The cooperative learning model of the type of Promotive Interaction (Face to Face Promotive Interaction) is a learning strategy that emphasizes the process of full student involvement to find the material being studied and connect it to real life situations, so that students are encouraged to be able to apply it in their lives. The advantages of the Face To Face Promotive Interaction cooperative learning model are that it can train students to be more active and train cooperation, students can master the lesson in a short time and each student can fill one So, teachers are expected to be able to apply this model in learning to make learning more interesting and fun and to help students train their communication and interaction skills among students.